2011
DOI: 10.1002/adsc.201100439
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation Processes by Pyridoxal Dioxomolybdenum(VI) (Pre)Catalysts Without Organic Solvent

Abstract: Molybdenum(VI) pyridoxal thiosemicarbazonato complexes have proved to be efficient catalysts in the olefinic epoxidation of cyclooctene by aqueous TBHP in the absence of an organic solvent. High activity and selectivity have been obtained with a catalyst loading of just 0.05% molybdenum in the case of one mononuclear (pre)catalyst (TOF 3360 h À1) under solvent-free conditions. The influence of methanol on the activity and selectivity has been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Catalytic applications of molybdenum complexes in organic transformations [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][31][32][33][34][35][36] and oxidation of sulfides [37][38][39] have also been explored, while oxidative bromination of organic substrates, a reaction normally promoted by vanadium haloperoxidase enzymes [40][41][42], has rarely been studied [32,43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic applications of molybdenum complexes in organic transformations [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][31][32][33][34][35][36] and oxidation of sulfides [37][38][39] have also been explored, while oxidative bromination of organic substrates, a reaction normally promoted by vanadium haloperoxidase enzymes [40][41][42], has rarely been studied [32,43].…”
Section: Introductionmentioning
confidence: 99%
“…The tendency of molybdenum to form stable complexes with oxygen, nitrogen and sulfur donor containing ligands has led to the development of high-valent molybdenum Schiff base complexes which are effective catalysts both in homogeneous and heterogeneous reactions [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The performance of these complexes varies noticeably with the nature of the ligands and the available coordination sites [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum(VI) dioxo or oxodiperoxo compounds are commonly encountered in oxidation catalysis. It has been shown that mononuclear peroxo and mono-oxo bridged dinuclear molybdenum complexes are active catalysts for the epoxidation of olefins and nonfunctionalized olefins with t-butylhydroperoxide TBHP as oxygen donor [8,[13][14][15]. The epoxidation of olefins catalyzed by a large family of complexes with MoO 2 X 2 (N-N) 2 or MoO 2 X 2 (N-O) 2 formula where N-N or N-O are bidenate ligands and X = Cl, Br or Me has been previously reported [10,11,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Some molybdates show antiviral, antitumoral or antibiotic activity [5][6][7]. They are also known as efficient catalysts for the oxidation of various organic compounds with different oxygen donors like ROOH [8][9][10][11][12][13][14][15][16][17][18][19][20] and H 2 O 2 [21][22][23][24][25][26][27][28][29]. Molybdenum(VI) dioxo or oxodiperoxo compounds are commonly encountered in oxidation catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneous molybdenum complexes have potential catalytic applications in the oxidation and oxidative bromination of organic substrates including oxidation of sulfides [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. However, immobilizations of these homogeneous catalysts on solid support and exploit them as potential industrial catalysts find limited entry in the literature [6][7][8]29].…”
Section: Introductionmentioning
confidence: 99%